Ahmad Haidir big talent in reciting poetry - Juwairiah, Osman; Siti Nur Azwin, Zulkapri (2020)
PEKAN, 9 December 2020 - Keen interest in poetry recitation prompted Universiti Malaysia Pahang (UMP) student, Ahmad Haidir Muhamad, 23, to participate and represent the university in the IPT 2020 Poetry Recitation Competition organised by Universiti Kebangsaan Malaysia (UKM) and Dewan Bahasa dan Pustaka (DBP).